Chromatin repair after oxidative stress: Role of PARP-mediated proteasome activation - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2010)
Oxidative stress is an inevitable process in the nucleus, especially in antitumor chemotherapy, and adaptation by defense mechanisms seems to be one element in the development of long-term resistance to many chemotherapeutic drugs. In this study, a potential chromatin repair mechanism during oxidative stress was investigated in HT22 cells. The 20S proteasome has been shown to be largely responsible for the degradation of oxidatively modified histone proteins in the nucleus. Poly(ADP-ribosyl)ation reactions also play an important role in DNA repair as a consequence of oxidative damage and single-strand breaks. Such a reaction may occur also with the 20S proteasome-with a known increase in enzymatic activity-and also with histones-reducing their proteolytic susceptibility as shown for the first time here. After hydrogen peroxide treatment of HT22 cells, degradation of the model peptide substrate suc-LLVY-MCA and degradation of oxidized histones by nuclear proteasome increased. During the removal of protein carbonyls, single-strand breaks and 8-hydroxy-2'-deoxyguanosine, proteasome, and poly(ADP-ribose) polymerase-1 enzymes were shown to play tightly interacting roles. Our results following the repair of oxidative damage show the proteolytic activation of proteasome concerning poly(ADP-ribosyl)ation together with a decline in poly(ADP-ribosyl)ation of oxidized histones, leading to a selective recognition of oxidatively modified histones. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Protein oxidation; Oxidative stress; Histone degradation; Proteasome activation; PARP-1; Free radicals; ADP-RIBOSE-POLYMERASE; POLY(ADP-RIBOSE) POLYMERASE; CANCER-CHEMOTHERAPY; NUCLEAR PROTEASOME; HYDROGEN-PEROXIDE; MAMMALIAN-CELLS; 20S PROTEASOME; DNA-DAMAGE; DEGRADATION; INHIBITION